The effects of the accession to the European Union on the evolution of Romania's cereal sector - Mihaela Kruzslicika (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The paper intends to examine the effects of the accession to the European Union on Romania's cereal sector, in the period 2007-2016, in terms of evolution of areas cultivated with wheat and maize, production in volume and value terms, consumption and self-sufficiency, exports and imports, as well as the evolution of prices. The results reveal that unlike other sectors, the accession has steadily contributed to Romania's cereal sector revigoration. Although yields in Romania are still substantially below those of the major European cereal producing countries, a steady growth trend can be noticed after 2007, due to the European funds that have allowed easier access to technological resources on the community market, and to a tendency for land consolidation, these advanced technologies being used more efficiently. The self-sufficiency degree has been reached and the trend is increasing, as it can be seen from the trade balance for cereals.
Keywords: Q01; Q10; Q12; Q13; 330; production; prices; productivity; cereals; consumption; trade; Romania